DNA methylation study of Huntington’s disease and motor progression in patients and in animal models - Ake T. Lu (Nature Portfolio, 2020)
Although Huntington’s disease (HD) is a well-studied genetic disorder, less is known about the epigenetic changes underlying it. Here, the authors characterize DNA methylation levels in tissues from patients, a mouse huntingtin (Htt) gene knock-in model, and a transgenic HTT sheep model, and provide evidence that HD is accompanied by DNA methylation changes in these three species.